Integrated UPLC-Q/TOF-MS Technique and MALDI-MS to Study of the Efficacy of YiXinshu Capsules Against Heart Failure in a Rat Model - Xu, Jing; Li, Xianyu; Zhang, Fangbo; Tang, Liying; Wei, Junying; Lei, Xiaoqing; Wang, Huanhuan; Zhang, Yi; Li, Defeng; Tang, Xuan; Li, Geng; Tang, Shihuan; et al. (Frontiers in Pharmacology, 2019)
Background: Yixinshu Capsules (YXSC) are widely used in Chinese medicine for the treatment of cardiovascular diseases. However, the therapeutic mechanisms of action are not well understood. Method: In this study, a metabonomic approach based on integrated UPLC-Q/TOF-MS technique and MALDI-MS was utilized to explore potential metabolic biomarkers that may help increase the understanding of heart failure (HF) and in order to assess the potential mechanisms of YXSC against HF. Plasma metabolic profiles were analyzed by UPLC-Q/TOF-MS with complementary hydrophilic interaction chromatography and reversed-phase liquid chromatography. Moreover, time-course analysis at the second, fourth and tenth week after permanent occlusion was conducted. In an effort to identify a more reliable potential metabolic marker, common metabolic markers of the second, fourth and tenth week were selected through multivariate data analysis. Furthermore, MALDI-MS was applied to identify metabolic biomarkers in the blood at apoptotic positions of heart tissues. Results: The results showed that HF appeared at the fourth week after permanent occlusion based on echocardiographic assessment. Clear separations were observed between the sham and model group by loading plots of orthogonal projection to latent structure discrimination analysis (OPLS-DA) at different time points after permanent occlusion. Potential markers of interest were extracted from the combining S-plots, variable importance for the projections values (VIP > 1) and t-test (p < 0.05). Twenty-one common metabolic markers over the course of the development and progression of HF after permanent occlusion were identified. These were determined to be mainly related to disturbances in fatty acids, phosphatidylcholine, bile acids, amino acid metabolism and pyruvate metabolism. Of the metabolic markers, 16 metabolites such as palmitoleic acid, arachidonic acid and lactic acid showed obvious changes (p < 0.05) and a tendency for returning to baseline values in YXSC-treated HF rats at the tenth week. Moreover, four biomarkers, including palmitoleic acid, palmitic acid, arachidonic acid and lactic acid, were further validated at the apoptotic position of heart tissue using MALDI-MS, consistent to the variation trends in the plasma. Conclusions: Taken in concert, our proposed strategy may contribute to the understanding of the complex pathogenesis of ischemia-induced HF and the potential mechanism of YXSC.